(untitled) (Economic and Political Thought, 2013)
The focus of this article is René Descartes’ bold claim that his method as presented in the Discourse on Method, will revolutionize science as well as philosophy. The author of this article reviews each chapter of the Discourse trying to establish what exactly Descartes had in mind and if he delivered what he had promised. The findings of the article are disappointing. Descartes skillfully uses rhetorical techniques to win his audience and to gain publicity, yet in fact he proposes no more than just four rules of conducting research inserted in chapter II. The remaining five chapters are either loosely connected with the main theme (chapters I and IV) or are entirely off the topic (chapters III, V and VI). Chapter IV, probably the most famous in the Discourse because of its cogito ergo sum principle, also has little in common with Descartes’ pledge. The author concludes that if there is anything worthy in the Discourse, it is its adolescent boldness and challenge to the establishment of Descartes’ time. If, however, we take his Discourse at face value, then we must conclude that Descartes fails to fulfill his promise and engages mainly in self-promotion.